Spontaneous multiple cervical artery dissections after alemtuzumab. (March 2020) - Durand-Dubief, Françoise; Marignier, Romain; Berthezene, Yves; Cottin, Judith; Nighoghossian, Norbert; Vukusic, Sandra
We report a case of multiple cervical artery dissections that occurred 4 days after a first course of alemtuzumab in a woman with relapsing–remitting multiple sclerosis and discuss its potential relationship and mechanisms of action. In particular, an arterial inflammatory process, secondary to cytokine release, could potentially lead to intimal thickening, luminal irregularities, stenosis, and ultimately occlusion. Occurrence of an unexpected serious adverse event, in our case, multiple cervical artery dissections, especially in a close time window after drug administration, questions a potential causal relationship with the drug or a simple coincidence.